Ultra-high strength steel with excellent plasticity and its manufacturing method
A carbon-silicon-manganese steel composition and continuous annealing process enhance both tensile strength and plasticity, addressing the limitations of existing high-strength steels by achieving high strength and formability with cost-effective manufacturing.
Patent Information
- Application Number
- JP2022575846
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-11
- Filing Date
- 2021-06-09
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-06-09
AI Technical Summary
Existing high-strength steels face challenges in achieving both ultra-high tensile strength and excellent plasticity due to limitations in microstructure and alloying element composition, leading to high material costs and complex manufacturing processes.
A compositional design of carbon-silicon-manganese steel with controlled amounts of C, Si, and Mn, combined with a manufacturing process involving continuous casting and continuous annealing, to achieve a microstructure of 20-40% ferrite, 50-70% martensite, and stable austenite, without expensive alloying elements.
The resulting steel exhibits yield strength of 850-1000 MPa, tensile strength of 1180-1300 MPa, uniform elongation of ≥11%, and break elongation of 15-20%, with improved formability and reduced production costs, suitable for automotive safety structural products.
Smart Images

Figure 0007617955000006 
Figure 0007617955000007 
Figure 0007617955000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel grade and a method for producing the same, in particular to a high strength steel grade and a method for producing the same. [Background technology]
[0002] In recent years, advanced high-tensile steels for automobiles have been widely used in the automobile manufacturing industry for the purposes of reducing vehicle weight, achieving energy conservation, improving crashworthiness, and reducing manufacturing costs. Advanced high-tensile steels are currently the most comprehensively competitive lightweight vehicle body material, because they allow the thickness of steel plates to be reduced due to improved steel plate strength while at the same time maintaining excellent forming performance.
[0003] Advanced high strength steels based on the transformation induced plasticity (TRIP) effect have high strength and good ductility at the same time. From the microstructural point of view, TRIP steels are composed of ferrite, bainite and residual The phase structure of TRIP steels is limited by its further strength improvement, but the strength of TRIP steels can be further increased by using martensite instead of bainite as the main strengthening phase. For advanced high-strength steels based on the TRIP effect, the main factors that determine their ductility are the morphology, volume fraction, and stability of the austenite remaining in the steel, and residual The stability of austenite is closely related to its size and carbon content.
[0004] Considering the strength and ductility of steel plates, conventional advanced high-tensile steels mainly contain many alloying elements such as Cr, Mo, Nb, Ti, and B in addition to the basic carbon-manganese steel composition. However, this not only results in high material costs, but also in difficulties in manufacturing, such as steelmaking, hot rolling, and cold rolling.
[0005] For example: a Chinese patent document (Patent Publication CN104245971A, disclosure date December 24, 2014, titled "High-strength cold-rolled steel plate and manufacturing method thereof") disclosed a high-strength steel plate. In the technical solution disclosed in this patent document, the composition is: C: 0.1%-0.3%, Si: 0.4%-1.0%, Mn: 2.0%-3.0%, Cr≦0.6%, Si+0.8Al+Cr: 1.0%-1.8%, Al: 0.2%-0.8%, Nb<0.1%, Mo<0.3%, Ti<0.2%, V<0.1%, Cu<0.5%, Ni<0.5%, S≦0.01%, P≦0.02%, N≦0.02%, B<0.005%, Ca<0.005%, Mg<0.005%, REM<0.005%, the rest being Fe and unavoidable impurities. The microstructure (volume %) is: residual Austenite 5%~20%, bainite + bainite ferrite + tempered martensite ≧80%, polygonal ferrite ≦10%, martensite-austenite composition ≦20%. I should explain that the steel composition according to this technical proposal requires the addition of a certain amount of Cr and Mo, and its tensile strength ≧980MPa and elongation rate are only about 14%, which is not advantageous in terms of cost and formability of steel for automotive parts.
[0006] Also, for example, a Chinese patent document (Patent Publication CN106574342A, disclosed on April 19, 2017, entitled "High-strength steel plate and its manufacturing method, and manufacturing method for high-strength galvanized steel plate") disclosed a high-strength steel plate. In the technical solution disclosed in this patent document, the manufacturing method is as follows: a steel slab satisfying the compositional conditions is heated to 1100-1300°C, the exit side temperature of the finish rolling is 800-1000°C, the average winding temperature is 450-700°C, the steel sheet is held at a temperature of 450°C to Ac1 for 900-36000s after pickling, cold rolling is performed with a rolling reduction of 30% or more, the steel sheet is heated to 820-950°C and subjected to a first annealing, thereafter cooled to 500°C or below the Ms temperature under conditions of an average cooling rate of 15°C / s or more, reheated to 740-840°C and subjected to a second annealing, cooled to 150-350°C at a cooling rate of 1-15°C / s, reheated to 350-550°C and kept at that temperature for 10s or more. The technical solution disclosed in this patent document requires hot rolling and two annealing treatments, which complicates the production process and increases the manufacturing cost, greatly limiting its application in the automotive field.
[0007] Further, for example: an international patent document (International Publication WO2018 / 116155, disclosure date June 28, 2018, entitled "HIGH-STRENGTH COLD ROLLED STEEL SHEET HAVING HIGH FORMABILITY AND A METHOD OF MANUFACTURING THEREOF") disclosed a high-strength cold-rolled steel sheet having high formability. In the technical solution disclosed in this patent document, the components are: C: 0.19%-0.24%, Mn: 1.9%-2.2%, Si: 1.4%-1.6%, Al: 0.01%-0.06%, Cr: 0.2%-0.5%, P≦0.02%, S≦0.003%, and optionally one or more of: Nb: 0.0010%-0.06%, Ti: 0.001%-0.08%, V: 0.001%-0.1%, Ca: 0.001%-0.005%, with the balance being Fe and unavoidable impurities. It should be noted that the steel grade according to this technical solution has a tensile strength of ≧1150MPa, an elongation of ≧13%, and a hole expansion ratio of ≧30%. Although the tensile strength is high, the addition of a large amount of Cr, Nb, and Ti makes it unsuitable for automotive steel, which has very strict cost constraint requirements. Summary of the Invention [Problem to be solved by the invention]
[0008] One object of the present invention is to provide an ultra-high tensile steel with excellent plasticity, which adopts a simple composition design in consideration of the strength and ductility of the steel plate, and fully utilizes the influence law of C, Si and Mn on the phase transformation of the material, so that the ultra-high tensile steel with excellent plasticity has a yield strength of 850-1000 MPa, a tensile strength of 1180-1300 MPa, a uniform elongation of ≥ 11%, and an elongation at break of 15%-20%, and has good application prospects and value. [Means for solving the problem]
[0009] To achieve the above object, the present invention provides an ultra-high strength steel with excellent plasticity, the mass percentages of the chemical elements being as follows: C: 0.26~0.30wt%; Si: 0.8-1.00wt%; Mn: 2.80-3.30wt%; Al: 0.04-0.08wt%; The remainder is Fe and other unavoidable impurities.
[0010] The technical solution of the present invention adopts the composition design of ordinary carbon silicon manganese steel, and fully utilizes the influence law of C, Si, and Mn on the phase transformation of materials, thereby achieving a balance between high strength and high ductility of the high tensile steel of the present invention, and finally obtaining a steel plate product with excellent performance. Specifically, the design principle of each chemical element is as follows: C: In the ultra-high tensile steel with excellent plasticity according to the present invention, C is the most important solid solution strengthening element, and can effectively maintain the strength of the steel. The higher the mass percentage of C in the steel, residual The austenite fraction increases, and when distributed residual The higher the concentration of C in the austenite, residual It is advantageous for enhancing the stability of austenite, and the TRIP effect increases the ductility of the material. However, it should be noted that if the C content in the steel is too high, the weldability of the steel decreases, and if the mass percent of C in the steel exceeds 0.30%, many twins are likely to appear after quenching, increasing the crack sensitivity. Therefore, in the ultra-high tensile steel with excellent plasticity according to the present invention, the mass percent of C is 0.26 to 0.30 wt%.
[0011] In a preferred embodiment, the mass percentage of C may be 0.26-0.28 wt%.
[0012] Si: In the ultra-high strength steel with excellent plasticity according to the present invention, Si strongly suppresses the formation of cementite during the distribution process, and carbon residual Promotes collection in austenite, residualIt is possible to improve the stability of austenite. To effectively suppress cementite, the Si content must be at least 0.8%. It should be noted that if the Si content in the steel is too high, the high temperature plasticity of the steel is reduced and the defect rate during hot rolling increases. At the same time, if the Si content is too high, stable oxides are formed on the steel sheet surface, which has a negative effect on the subsequent pickling process. Therefore, in the ultra-high tensile steel with excellent plasticity according to the present invention, the mass percent of Si is 0.8-1.00 wt%.
[0013] In a preferred embodiment, the mass percentage of Si may be 0.9-1.00 wt%.
[0014] Mn: In the ultra-high tensile steel with excellent plasticity according to the present invention, Mn can expand the austenite phase region, lower the Ms and Mf points, effectively improve the stability of austenite and the hardenability of the steel, and reduce the critical transformation rate. residual It is advantageous for preserving austenite at room temperature. At the same time, Mn is an important solid solution strengthening element. However, it should be noted that if the Mn content in steel is too high, the corrosion resistance and weldability deteriorate, and at the same time, the crystal grains tend to become coarse, reducing the plasticity and toughness of the steel. Therefore, in the ultra-high tensile steel with excellent plasticity according to the present invention, the mass percentage of Mn is 2.80 to 3.30 wt%.
[0015] In a preferred embodiment, the mass percentage of Mn may be between 2.9 and 3.1 wt%.
[0016] Al: In the ultra-high tensile steel with excellent plasticity according to the present invention, when Al exists in a solid solution state, it can not only increase stacking fault energy, but also suppress the precipitation of cementite and the transformation from γ to martensite, and increase the stability of austenite. In addition, Al can form insoluble points finely dispersed with C and N, and can refine crystal grains, but the strengthening effect of Al is weaker than that of Si, and the ability to stabilize austenite is also weaker than that of Si. If the mass percentage of Al in the steel is too high, a large amount of intervening oxides is easily formed, which is disadvantageous to the cleanliness of the steel liquid. Therefore, in the ultra-high tensile steel with excellent plasticity according to the present invention, the mass percentage of Al is 0.04 to 0.08 wt%.
[0017] Furthermore, in the ultra-high strength steel with excellent plasticity according to the present invention, the mass percentage of each chemical element satisfies at least one of the following conditions: C: 0.26~0.28wt%; Si: 0.9-1.00wt%; Mn: 2.9-3.1wt%.
[0018] Furthermore, the ultra-high tensile steel with excellent plasticity according to the present invention further contains at least one of the following elements: 0 <Cr≦0.05wt%; 0 <Mo≦0.05wt%; 0 <Nb≦0.03wt%; 0 <Ti≦0.05wt%; 0 <V≦0.03wt%; 0 <B≦0.001wt%。
[0019] The above-mentioned Cr, Mo, Nb, Ti, V and B can all further improve the performance of the high tensile steel according to the present invention. For example, Cr and Mo can improve the hardenability of the steel and adjust the strength of the steel, but Cr collects on the surface of the steel sheet and affects the welding performance. And if the mass percentage of Mo is too high, the cold rolling strain yield strength of the steel increases. Also, for example, Nb, Ti and V can form fine carbides with C and promote the refinement of the structure, but the formation of such fine carbides can also cause problems such as: residualThe accumulation of C in austenite residual It is disadvantageous to the stabilization of austenite. And the main effect of B is to improve the hardenability of steel. B is easy to segregate at the austenite crystal boundary, delaying the transformation from austenite to ferrite, and has obvious effects even at a low content, but if the mass percentage of B is too high, the steel strength will increase, which is disadvantageous to good forming. Therefore, the mass percentage of B should be 0. <B≦0.001%にしてもいい。
[0020] In addition, the addition of the above elements will increase the cost of the material. Therefore, taking into consideration the performance and cost restrictions, the technical solution of the present invention preferably includes at least one of the above elements.
[0021] Furthermore, in the ultra-high tensile steel with excellent plasticity according to the present invention, each chemical element satisfies at least one of the following conditions: 0 <Cr≦0.03wt%; 0 <Mo≦0.03wt%; 0 <Nb≦0.01wt%; 0 <Ti≦0.03wt%; 0 <V≦0.01wt%。
[0022] Furthermore, in the ultra-high strength steel with excellent plasticity according to the present invention, other unavoidable impurities are as follows: P≦0.01wt%, S≦0.01wt%, N≦0.006wt%.
[0023] In the above technical proposal, P, S and N are all impurity elements. P has the effect of solid solution strengthening, inhibiting the formation of carbides, residualAlthough it is advantageous for improving the stability of austenite, if the mass percentage of P is too high, the crystal boundaries will be weakened, the brittleness of the material will increase, and the weldability will deteriorate. In other words, the positive effects of P are weaker than the negative effects, so the mass percentage of P is preferably P≦0.01wt%. As for N, if the mass percentage of N is too high, it will make steelmaking and continuous casting difficult and is disadvantageous for limiting inclusions, so the mass percentage of N is preferably N≦0.006wt%. Also, if the mass percentage of S element in steel is too high, the plasticity of the material will obviously deteriorate, so the mass percentage of S is S≦0.01wt%.
[0024] Furthermore, the mass percentages of the chemical elements of the ultra-high strength steel with good plasticity according to the invention are: C: 0.26 to 0.30 wt%, preferably 0.26 to 0.28 wt%; Si: 0.8 to 1.00 wt%, preferably 0.9 to 1.00 wt%; Mn: 2.80-3.30 wt%, preferably 2.9-3.1 wt%; Al: 0.04-0.08wt%; Cr:≦0.05wt%, preferably 0.03wt%; Mo: ≦0.05wt%, preferably 0.03wt%; Nb: ≦0.03wt%, preferably 0.01wt%; Ti: ≦0.05wt%, preferably 0.03wt%; V:≦0.03wt%, preferably 0.01wt%; B:≦0.001wt%; P: ≤ 0.01 wt%; S: ≤ 0.01wt%; N ≤ 0.006 wt%; The remainder is Fe and other unavoidable impurities.
[0025] Furthermore, in the ultra-high tensile steel with excellent plasticity according to the present invention, the microstructure (volume ratio) is 20% to 40% ferrite + 50% to 70% martensite + residual It is austenite.
[0026] Furthermore, in the ultra-high tensile steel with excellent plasticity according to the present invention, crystal grains of 10 μm or less account for 90% or more of the ferrite, and crystal grains of 5 μm or less account for 60% or more.
[0027] Furthermore, in the ultra-high tensile steel having excellent plasticity according to the present invention, residual Average austenite grain size ≦2 μm; and / or residual In one embodiment, in the ultra-high strength steel with excellent plasticity according to the present invention, residual The average grain size of austenite is 0.6-1.6 μm. In one embodiment, in the ultra-high strength steel with excellent plasticity according to the present invention, residual The average C content in austenite is 1.1-1.35wt%.
[0028] Furthermore, the ultra-high tensile steel excellent in plasticity according to the present invention has a yield strength of 850 to 1000 MPa, a tensile strength of 1180 to 1300 MPa, a uniform elongation of ≥ 11%, and a fracture elongation of 15% to 20%.
[0029] Another object of the present invention is to provide a method for producing the ultra-high tensile steel with excellent plasticity. This method combines a continuous casting process of a thin plate slab with a pickling or acid rolling process to obtain an ultra-high tensile steel with excellent plasticity after continuous annealing. This method is simple to produce, and the elongation of the resulting high tensile steel is further increased under similar strength conditions.
[0030] In order to achieve the above object, the present invention provides a method for producing the above-mentioned ultra-high tensile steel having excellent plasticity, comprising the following steps: (1) Smelting and continuous casting of thin slabs: The thickness of the slab at the outlet of the continuous casting is 55-60 mm; (2) heating; (3) Hot rolling: the thickness of the oxide film on the surface of the hot-rolled steel strip is ≦6 μm, and the content of (FeO+Fe3O4) in the oxide film on the surface of the hot-rolled steel strip is ≦40 wt%; (4) Pickling or pickling + cold rolling; (5) Continuous annealing: Anneal at 800-920°C, then slowly cool to 690-760°C at a cooling rate of 3-10°C / s to obtain a certain proportion of ferrite; then rapidly cool to 250-350°C, and cool at a rate of 50-100°C / s to convert the austenite to martensite; then reheat to 360-460°C, keep at that temperature for 100-400s, and finally cool to room temperature.
[0031] In the technical solution of the present invention, continuous casting of thin plate slabs is adopted in step (1), which eliminates the rough rolling process, reduces the amount of hot rolling distortion, and maintains the steel plate performance in the subsequent steps (4) and (5). In addition, the continuous casting of thin plate slabs adopted in step (1) can fully utilize the heat of the plate slab and reduce the energy consumption used for heating, resulting in a more uniform ferrite or ferrite + pearlite structure, which is favorable for maintaining a certain amount of fine grain ferrite in the microstructure of the finished product in the subsequent step (5), which is favorable for improving the uniformity of the structure, and improving the plasticity.
[0032] In step (3), the thickness of the oxide film on the surface of the hot-rolled steel strip is ≦6μm, and the (FeO+Fe3O4) in the oxide film on the surface of the hot-rolled steel strip is ≦40wt%, which is favorable for the progress of the subsequent step (4) and has an important effect on the performance of the steel sheet obtained after continuous annealing. Because: in the technical solution of the present invention, FeO and Fe3O4 are less susceptible to pickling than Fe2O3, but by controlling the thickness of the oxide film on the surface of the hot-rolled steel strip and making the (FeO+Fe3O4) in the oxide film on the surface of the hot-rolled steel strip ≦40wt%, the effect of pickling is improved, and a pickled sheet surface that can be directly used for continuous annealing can be obtained. And since the pickled sheet can be directly subjected to continuous annealing, the amount of structural distortion of hot rolling can be reduced, and the steel sheet structure can be mainly ferrite and pearlite or bainite, so that under the same continuous annealing conditions, the strength of the material can be reduced, the structure can be more uniform, and excellent ductility can be obtained.
[0033] Then, in step (5), the annealing temperature is set to 800-920°C, so that a uniform austenite structure or austenite + ferrite structure can be formed; then, the ferrite content in the structure is further adjusted by slowly cooling to 690-760°C at a cooling rate of 3-10°C / s, and the material can be further formed; then, the material is cooled to 250-350°C (i.e., between the Ms and Mf temperatures) at a rate of 50-100°C / s. This is because: in the cooling process, the critical cooling rate must be 50°C / s or more so that only the martensite phase transformation occurs, and if the cooling rate exceeds 100°C / s, the production cost will increase significantly. At this time, the austenite is partially transformed into martensite, so that the steel can maintain its high strength; reheating to 360-460°C and keeping it at the same temperature for 100-400s allows the carbon to be distributed in the martensite and austenite, and a certain amount of high carbon is formed. residual By forming austenite and holding it stable at room temperature, the TRIP effect significantly improves the work hardening ability and formability of the steel, resulting in an ultra-high strength steel plate with excellent plasticity. The reason for setting the above distribution process is that when the reheating temperature is less than 360°C or the reheating time is less than 100s, the stabilization process of the austenite remaining in the steel is insufficient, and the final stabilization process at room temperature is insufficient. residual Insufficient austenite content; when the reheating temperature exceeds 460℃ or the reheating time exceeds 400s, the steel will suffer obvious temper softening, and finally the strength of the material will be obviously reduced.
[0034] The ultra-high tensile steel of the present application utilizes a high carbon and high manganese composition design and a mechanism for refining ferrite crystal grains, so that during the continuous annealing process, the number of nucleation points for the reverse phase transformation of austenite increases, while the size is further refined and can be kept stable up to room temperature. residual Average austenite grain size ≤ 2 μm; residual The average C content in austenite is ≥ 1.1%. In addition, due to the use of high Si design, the martensite formed by rapid cooling does not decompose during the distribution process, so the content of martensite in the structure is maintained, and the strength of the steel is maintained.
[0035] Furthermore, in the manufacturing method according to the present invention, in step (1), the pulling speed of the controlled continuous casting is set to 2 to 5 m / min.
[0036] Furthermore, in the manufacturing method according to the present invention, in step (2), the plate slab is heated to 1200 to 1300°C.
[0037] Furthermore, in the manufacturing method according to the present invention, in step (3), the finish rolling temperature is set to 860 to 930°C, and the winding temperature is set to 450 to 600°C.
[0038] Furthermore, in the manufacturing method according to the present invention, when the step of pickling+cold rolling is adopted in step (4), the amount of distortion is set to 40% to 70%.
[0039] Further, in the manufacturing method according to the present invention, in step (5), the continuous annealing process satisfies at least one of the following conditions: The annealing temperature is 820-870°C; Cool slowly to 700-730℃ at a cooling rate of 3-10℃ / s; Quench to 270-330°C; After quenching, heat further to 400-430℃ and keep at that temperature for 150-300s; The volume content of hydrogen gas in the reducing atmosphere in the continuous annealing furnace is set to 10 to 15%. Effect of the Invention
[0040] The ultra-high tensile steel with excellent plasticity and the manufacturing method thereof according to the present invention have the following advantages and beneficial effects compared to the prior art: The high-tensile steel of the present invention is based on carbon-silicon-manganese steel, and does not contain any expensive alloying elements. By optimizing the proportion of carbon-silicon-manganese, a high-strength cold-rolled steel sheet with excellent ductility can be obtained.
[0041] The manufacturing method of the present invention has a unique production process and adopts continuous casting technology for thin plate slabs, which has inherent advantages in terms of structure uniformity and segregation control. The obtained ultra-high tensile steel can significantly increase elongation under similar strength conditions, so it has good application prospects in automobile safety structures, especially suitable for manufacturing vehicle structures and safety products with complex shapes and high requirements for forming performance, such as A / B pillars, waist reinforcements, side members, bumpers, etc. [Brief description of the drawings]
[0042] [Figure 1] FIG. 1 shows a photograph of the microstructure of the ultra-high tensile steel of Example 4. [Diagram 2] FIG. 2 shows an EBSD photograph of the phase composition of the ultra-high tensile steel of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] The following provides a more detailed description of the ultra-high tensile steel with excellent plasticity and the manufacturing method thereof according to the present invention with reference to the drawings and specific examples, but the description is not intended to limit the technical solution of the present invention.
[0044] Examples 1-24 and Comparative Examples 1-3 The highly plastic ultra-high strength steel of Examples 1-24 was produced by the following steps: (1) Smelting and continuous casting of thin slabs were carried out with the chemical composition shown in Table 1. The thickness of the slab at the outlet of the continuous casting was 55-60 mm, and the pulling speed of the continuously cast slab was 2-5 m / min.
[0045] (2) Heating: The plate slab was heated to 1200-1300°C. (3) Hot rolling: The thickness of the oxide film on the steel strip surface after hot rolling is ≦6 μm, and the (FeO+Fe3O4) content in the oxide film on the steel strip surface after hot rolling is ≦40 wt%, the finish rolling temperature is 860 to 930°C, and the winding temperature is 450 to 600°C.
[0046] (4) Pickling or pickling + cold rolling: When the pickling + cold rolling step is adopted, the distortion amount is set to 40% to 70%.
[0047] (5) Continuous annealing: Annealing at 800-920°C, followed by slow cooling at a cooling rate of 3-10°C / s to 690-760°C to obtain a certain proportion of ferrite; further quenching to 250-350°C, followed by cooling at a rate of 50-100°C / s to convert the austenite portion to martensite; then reheating to 360-460°C, keeping the temperature for 100-400s, and finally cooling to room temperature.
[0048] It should be noted that in a preferred embodiment, in step (5), the parameters further satisfy at least one of the following: The annealing temperature was 820-870°C; The mixture was cooled slowly to 700-730°C at a cooling rate of 3-10°C / s; Quenched to 270-330°C; After quenching, it was further heated to 400-430℃ and kept at that temperature for 150-300s; The volume content of hydrogen gas in the reducing atmosphere in the continuous annealing furnace was set to 10 to 15%.
[0049] Comparative Example 1-3 was produced by the normal process. Table 1 shows the mass percent composition ratios of the chemical elements in the ultra-high tensile steels with excellent plasticity of Examples 1-24 and the comparative steels of Comparative Examples 1-3.
[0050] [Table 1]
[0051] Tables 2-1 and 2-2 show specific process parameters for the ultra-high tensile steels with excellent plasticity of Examples 1-24 and the comparative steels of Comparative Examples 1-3.
[0052] [Table 2-1]
[0053] [Table 2-2]
[0054] Table 3 shows the results of measuring the mechanical properties of the ultra-high tensile steels with excellent plasticity of Examples 1-24 and the comparative steels of Comparative Examples 1-3. The measurements were performed according to ISO 6892:1998 (Room temperature tensile test method for metallic materials), P14 (A50) tensile standard.
[0055] [Table 3]
[0056] As can be seen from Table 3, the ultra-high tensile steel with excellent plasticity of Example 1-24 of the present application not only maintained its strength but also had excellent ductility, with a yield strength YS of 850 to 1000 MPa, a tensile strength TS of 1180 to 1300 MPa, a uniform elongation UEL of ≥ 11%, and a fracture elongation TEL of 15% to 20%.
[0057] Table 4 shows the results of observation of the microstructure of the ultra-high tensile steel with excellent plasticity of Example 1-24.
[0058] [Table 4]
[0059] As can be seen from Tables 3 and 4, the microstructure of the ultra-high tensile steel with excellent plasticity of Example 1-24 of the present application is 20% to 40% ferrite + 50% to 70% martensite + residual The austenite has ferrite in which crystal grains of 10 μm or less account for 90% or more and crystal grains of 5 μm or less account for 60% or more. residual Average austenite grain size ≦2 μm; and / or residualIn the austenite, the average C content is ≧1.1 wt%. Therefore, the ultra-high tensile steels with excellent plasticity in various embodiments of the present invention have a certain amount of fine grain ferrite and good structure uniformity, so that the ultra-high tensile steels of each embodiment have not only ultra-high strength but also excellent plasticity.
[0060] FIG. 1 shows a photograph of the microstructure of the ultra-high tensile steel of Example 4. FIG. 2 shows an EBSD photograph of the phase composition of the ultra-high tensile steel of Example 4.
[0061] As can be seen by combining Figures 1 and 2, the microstructure of the ultra-high tensile steel of Example 4 is 20% to 40% ferrite + 50% to 70% martensite + residual The austenite has ferrite in which crystal grains of 10 μm or less account for 90% or more and crystal grains of 5 μm or less account for 60% or more. residual Average austenite grain size ≦2 μm; and / or residual In austenite, the average C content is ≧1.1wt%.
[0062] As described above, the ultra-high strength steel of the present invention is based on carbon silicon manganese steel, does not contain any expensive alloying elements, optimizes the blending ratio of carbon silicon manganese, and employs continuous thin slab casting technology, thereby having inherent advantages in terms of structure uniformity and segregation control.
[0063] The manufacturing method of the present invention has a simple production process, and the obtained ultra-high tensile steel can exhibit a significantly increased elongation under similar strength conditions, so that it has good application prospects in automobile safety structures, and is particularly suitable for manufacturing vehicle structures and safety products that have complex shapes and high requirements for forming performance, such as A / B pillars, waist reinforcements, side members, bumpers, etc.
[0064] It should be explained that the part of the prior art within the protection scope of the present invention is not limited to the examples provided in this application, and any technical solutions that do not contradict the technical solutions of the present invention, including but not limited to prior patent documents, prior disclosure publications, prior disclosure applications, etc., fall within the protection scope of the present invention.
[0065] Furthermore, the combination methods of each technical feature in this application are not limited to the combination methods described in the claims or the combination methods described in the specific examples, and all technical features described in this application may be freely combined or combined in any manner as long as they are not inconsistent with each other.
[0066] Furthermore, it should be noted that the above-mentioned embodiments are merely specific embodiments of the present invention, and the present invention is not limited to the above-mentioned embodiments, and similar changes and modifications can be directly obtained or easily conceived by those skilled in the art from the disclosure of the present invention, and therefore, they are within the protection scope of the present invention.
Claims
1. 1. An ultra-high tensile cold rolled steel sheet with excellent plasticity, the mass percentages of chemical elements being as follows: C: 0.26-0.30wt%; Si: 0.8-1.00wt%; Mn: 2.80-3.30wt%; Al: 0.04-0.08wt%; The balance is Fe and other unavoidable impurities. The ultra-high tensile cold rolled steel sheet has a microstructure of 20% to 40% ferrite + 50% to 70% martensite + retained austenite, in which crystal grains of 10 μm or less account for 90% or more of the ferrite and crystal grains of 5 μm or less account for 60% or more of the ferrite, an average crystal grain size of the retained austenite is ≦2 μm; and / or an average C content of the retained austenite is ≧1.1 wt%, The present invention provides an ultra-high tensile cold-rolled steel sheet having excellent plasticity, a yield strength of 850 to 1000 MPa, a tensile strength of 1180 to 1300 MPa, a uniform elongation of 11% or more, and a breaking elongation of 15% to 20%.
2. The ultra-high tensile cold-rolled steel sheet having excellent plasticity according to claim 1, wherein the mass percentage of each chemical element satisfies at least one of the following conditions: C: 0.26-0.28wt%; Si: 0.9-1.00wt%; Mn: 2.9 to 3.1 wt%.
3. The ultra-high tensile cold rolled steel sheet having excellent plasticity according to claim 1, further comprising at least one of the following elements: 0<Cr≦0.05wt%; 0<Mo≦0.05wt%; 0<Nb≦0.03wt%; 0<Ti≦0.05wt%; 0<V≦0.03wt%; 0<B≦0.001wt%.
4. The ultra-high tensile cold rolled steel sheet having excellent plasticity according to claim 3, wherein each chemical element satisfies at least one of the following conditions: 0<Cr≦0.03wt%; 0<Mo≦0.03wt%; 0<Nb≦0.01wt%; 0<Ti≦0.03wt%; 0<V≦0.01wt%.
5. The ultra-high tensile cold rolled steel sheet with excellent plasticity as claimed in claim 1, wherein other unavoidable impurities are as follows: P≦0.01wt%, S≦0.01wt%, N≦0.006wt%.
6. A method for producing an ultra-high tensile cold-rolled steel sheet having excellent plasticity according to any one of claims 1 to 5, comprising the following steps: (1) Smelting and continuous casting of thin slabs: the thickness of the slab at the outlet of the continuous casting is 55-60 mm; (2) Heating; (3) Hot rolling: The thickness of the oxide film on the surface of the hot-rolled steel strip is ≦6 μm, and the (FeO+Fe 3 O 4 )≦40 wt%; (4) pickling or pickling + cold rolling; (5) Continuous annealing: Anneal at 800-920°C, slowly cool at a cooling rate of 3-10°C / s to 690-760°C to obtain a certain proportion of ferrite; further rapidly cool to 250-350°C, and then change the cooling rate to 50-100°C / s to convert the austenite portion to martensite; then further heat to 360-460°C, keep at that temperature for 100-400s, and finally cool to room temperature.
7. The method according to claim 5, wherein in step (1), the pulling speed of the continuous casting is 2 to 5 m / min.
8. The method according to claim 5, wherein in step (2), the plate slab is heated to 1200 to 1300°C.
9. The manufacturing method according to claim 5, wherein in step (3), the finish rolling temperature is 860 to 930°C and the winding temperature is 450 to 600°C.
10. The manufacturing method according to claim 5, wherein in step (4), when the pickling + cold rolling step is adopted, the distortion amount is 40% to 70%.
11. The method of claim 5, wherein in step (5), the continuous annealing process satisfies at least one of the following: The annealing temperature is 820 to 870°C; Slowly cool to 700-730°C at a cooling rate of 3-10°C / s; Quench to 270-330°C; After quenching, the mixture is further heated to 400-430°C and kept at that temperature for 150-300s; The volume content of hydrogen gas in the reducing atmosphere in the continuous annealing furnace is set to 10 to 15%.
Citation Information
Patent Citations
High-strength hot-dip galvanized steel sheet with excellent workability and process for producing the same
JP2009203548A
High-strength cold-rolled steel sheet excellent in workability and impact resistance and method for manufacturing the same
JP2010196115A
High strength cold rolled steel sheet and production method thereof
JP2015034327A
High-formability ultra-high-strength cold-rolled steel sheet and its manufacturing method
JP2016503458A
Cold-rolled high-strength steel with a tensile strength of 1500 MPa or more and excellent formability, and its manufacturing method
JP2019534941A